Ball speed in women handball players: Analysis of different playing positions - Manchado, C.; Ferragut, C.; Abraldes, A.; Rodriguez, N.; Alcara, P.; Vila, H. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
The aim of this study was to describe the ball speed of different playing positions in female toplevel handball players. 130 professional female players of the Spanish 1st handball league agreed to participate in this study. These data indicate that position-specific ball speed depends on the main throw that is performed most often during training and matches.